Sociodemographic and Cultural Aspects of the Gayo Community in Exclusive Breastfeeding in the Work Area of the Pegasing Health Center, Central Aceh - Dewi, Nova Ratna; Hidayana; Irdayani (HM Publisher, 2023)
Exclusive breastfeeding is breastfeeding only, without additional fluids and other foods for the first 6 months. Economic, cultural, and sociodemographic factors are thought to influence mothers to keep working even though their babies still need exclusive breastfeeding. This study aimed to describe cultural and sociodemographic factors related to exclusive breastfeeding in the working area of the Pegasing Health Center, Central Aceh. This research is an observational study. A total of 73 mothers participated in this study. The inclusion criteria are mothers who have children aged 0-5 years, domicile in the Pegasing Health Center work area, and are willing to participate in this study. Sociodemographic data and the level of knowledge of mothers regarding exclusive breastfeeding were measured using a structured interview and questionnaire. Cultural aspects related to exclusive breastfeeding were explored through focus group discussions and in-depth interviews. The majority of participants had senior high school education (57.5%), family income was below the Central Aceh regional minimum wage (95.89%), and mothers' knowledge regarding exclusive breastfeeding was considered good (50.7%). Meanwhile, mothers considered that family support in breastfeeding was good (50.7%). However, support from health workers was considered to be lacking regarding exclusive breastfeeding (38.4%). Based on the results of the interviews, there are habits making up and myths about dena which inhibit exclusive breastfeeding in infants in the Gayo area. In conclusion, family income and cultural factors have a role in exclusive breastfeeding in the working area of the Pegasing Health Center, Central Aceh.